IR spectra of ethanol nanoclusters in a nitrogen cryomatrix. - Aldiyarov, A.; Zhexen, U.; Nurmukan, A.; Oman, Z.; Torebai, A. (Recent Contributions to Physics, 2019)
This article presents the results of investigations the processes of formation and properties of ethanol clusters formed by the cryomatrix isolation method in the process of condensation of ethanol and nitrogen from the gas phase onto a cooled metal substrate. The measurements were performed in the temperature range of 12–40 K with an initial vacuum in the chamber of at least 10–8 Torr. The concentration of ethanol in nitrogen ranged from 0.5 to 3%. The method of obtaining information about the state of ethanol molecules in the nitrogen matrix is based on the analysis of the absorption amplitudes of the bands corresponding to the vibrations of the ethanol molecule in the unbound state. In particular, the absorption amplitude of the deformation δ (OH) oscillation was measured at a frequency ν=1259 cm-1, which is a sign of the presence of monomers or dimers of ethanol in the object under consideration in the anti-conformal state. Based on the analysis of the reflection spectra, it is concluded that the nitrogen matrix contains ethanol polyaggregates formed during the condensation of a mixture of nitrogen and ethanol.